MTA1 Expression Correlates Significantly with Histologic Grade in Salivary Mucoepidermoid Carcinoma - Omar I Ahmed; Lehadh M Al-Azzawi; Mustafa G Taher (Diyala Journal of Medicine, 2019)
Background: Metastasis associated protein-1 (MTA1) has been a recently identified as a unique gene playing important role in tumorigenesis and progression of cancer cells. Objective:To evaluate MTA1 expression and its predictive value in determining histologic grade of salivary mucoepidermoid carcinoma (MEC).